Deteksi Dini Polutan: Menggunakan Geokimia untuk Memantau Logam Berat dalam Air Tanah - Hasan, Haslinda (Jurnal Ilmiah Multidisiplin Amsir, 2024)
This research examines the use of geochemical approaches for early detection of heavy metals in groundwater, a crucial issue in water resources management and environmental protection. Using qualitative research methods with a literature study approach, this research analyzes various secondary data sources to understand the effectiveness, challenges and opportunities for developing geochemical methods in monitoring groundwater quality. The research results show that the geochemical approach has significant advantages in detecting subtle changes in the chemical composition of groundwater, which can be an early indicator of heavy metal contamination. Geochemical parameters such as pH, electrical conductivity, and total dissolved solids (TDS) have proven to be effective as indicators of the presence of heavy metals. Additionally, stable isotope analysis allows identification of pollution sources, opening up opportunities for more targeted mitigation strategies. This research also reveals the importance of integrating geochemical methods with Geographic Information Systems (GIS) for spatial pollution risk mapping. However, gaps were found in the applicability of this method in various geological conditions, indicating the need for the development of more adaptive models. In conclusion, geochemical approaches offer a promising solution for early detection of heavy metals in groundwater, but require further research to overcome implementation challenges, especially in developing countries. This research makes an important contribution to efforts to protect groundwater resources and supports the achievement of sustainable development goals related to clean water and sanitation.